Transport of Particulate Organic Matter and Dissolved Organic Matter from Land to Ocean in Hokkaido, Japan (Dhaka University Journal of Science, 2015)
Both ?14C, ?13C for the particulate organic matter (POM) and 3-Dimensional Excitation and Emission Matrix spectroscopy (3D-EEM) for the dissolved organic matter (DOM) were used to study transport behavior from land to ocean in Hokkaido, Japan. The ?14C values of the Tokachi POC (particulate organic carbon) show similar variations to Ishikari. However, the variation range of the Tokachi of ?14C is smaller than that of the Ishikari POC. ?13C values for the Ishikari showed larger variation range than those of the Tokachi. The POC during spring snow-melting for the Ishikari and in autumn during heavy rain fall for the Tokachi were distinctive in the correlations of POC, ?14C, and ?13C.There were two different pathways in the correlations of POC content, ?14C, and water discharge for both river systems. The significant pathway during snow-melting found in the Ishikari and at autumn during heavy rain fall for the Tokachi. The Tokachi and the Ishikari River showed similar variations patterns of dissolved organic carbon (DOC) concentrations and relative fluorescence intensity (RFI). The run-off point of DOC and FA-like materials is similar to POC. Therefore, characteristics and export of POC and DOC may be controlled by water discharge in small rivers in sub-arctic zone. The both rivers showed averaged POC flux from 1.43~1.51 ¥ 1010 g/yr, DOC flux of 0.98~2.32 ¥ 1010 g/yr, and fulvic-like materials-carbon (FAC) flux of 0.70~1.22 ¥ 1010 g/yr. The percentages of POC, DOC, and FAC flux in two rivers during snow-melting and heavy rainfall were 78~95% and 25~ 42 %, respectively. The watersheds of the Ishikari and Tokachi are important in transport of POC from land to ocean, especially during snow-melting and heavy rain event. DOI: http://dx.doi.org/10.3329/dujs.v63i1.21768 Dhaka Univ. J. Sci. 63(1): 47-51, 2015 (January)